Study the effect of financial leverage on financial return An applied study of a sample of institutions in the Hassi-Messaoud region during the period (2009-2014) - Belkheir Bakkari; Abderahmane Daggoume (Dirassat Journal Economic Issue, 2017)
The objective of this study is to understand the impact of leverage and its effect on financial profitability. We selected a sample of five national oil companies operating in the HASSI Mesasaoud oil zone over a period of six years (from 2009 to 2014). We used the panel data model to study the relationship between leverage and financial profitability according to the statistical program (Eviews7). Our results have shown the existence of an inverse impact relationship between leverage and financial profitability and the components of the overall profit rate and asset turnover rate and the structural rate in this type of business. . As a result, the volume of financial debts should be reduced, which increases the financial charges, which in turn negatively affect financial profitability.